1982
DOI: 10.2307/3586471
|View full text |Cite
|
Sign up to set email alerts
|

Errors, Interaction, and Correction: A Study of Native-Nonnative Conversations

Abstract: In an investigation of native speaker (NS)‐nonnative speaker (NNS) conversations in social settings, we learn that only a small percentage (8.9%) of NNS errors were corrected by NSs. These corrections occurred in response to errors of fact, discourse, vocabulary, syntax, and omission. Since discourse and vocabulary errors were corrected more frequently than errors in syntax and omission, we recommend that the treatment of vocabulary in the ESL classroom be reexamined, and that serious consideration be given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 8 publications
3
78
2
Order By: Relevance
“…This research indicated that teachers' attempts at error correction were frequently ambiguous and inconsistent and, therefore, that the value of correction was not clearly demonstrated. Other studies explored error correction by NSs in more naturalistic conversations (Chun, Day, Chenoweth, & Luppescu, 1982;Day, Chenoweth, Chun, & Luppescu, 1984), which revealed that NSs rarely correct learners' errors in conversation.…”
Section: The Role Of Negative Feedback and Positive Evidence In L2 Acmentioning
confidence: 99%
“…This research indicated that teachers' attempts at error correction were frequently ambiguous and inconsistent and, therefore, that the value of correction was not clearly demonstrated. Other studies explored error correction by NSs in more naturalistic conversations (Chun, Day, Chenoweth, & Luppescu, 1982;Day, Chenoweth, Chun, & Luppescu, 1984), which revealed that NSs rarely correct learners' errors in conversation.…”
Section: The Role Of Negative Feedback and Positive Evidence In L2 Acmentioning
confidence: 99%
“…During this period and the following decades research centred on different aspects of error-making: the development of taxonomies for identifying and classifying errors (Dusková 1969, Burt and Kiparsky 1974, Politzer and Ramírez 1973, Corder 1981, Chun et al 1982, Dulay, Burt and Krashen 1982; the investigation of error gravity (Tomiyama 1980, Hughes and Lascaratou 1982, Davies 1985, McCretton and Rider 1993; and detailing the different causes of errors (Richards 1974, Odlin 1989, Gass and Selinker 1992, Ringbom 1992.…”
Section: The Rise and Fall Of Il Error Studiesmentioning
confidence: 99%
“…Although early studies raised considerable doubts as to the efficacy of feedback (e.g. Chaudron, 1977;Chun et al, 1982), recent studies provide substantial evidence on its effectiveness in SLA (Carroll & Swain, 1993;Ellis et al, 2001; Ferris,1997). Studies in the 1990s denote that providing feedback to students on both content and form may improve their learning and result in the development of their interlanguage system.…”
Section: Introductionmentioning
confidence: 99%